Measuring the RFI environment of the South African SKA site - Manners, Paul John (Rhodes University, Faculty of Science, Department of Physics and Electronics, 2007)
The Square Kilometre Array (SKA) Project is an international effort to build the world's largest radio telescope. It will be 100 times more sensitive than any other radio telescope currently in existence and will consist of thousands of dishes placed at baselines up to 3000 km. In addition to its increased sensitivity it will operate over a very wide frequency range (current specification is 100 MHz - 22 GHz) and will use frequency bands not primarily allocated to radio astronomy. Because of this the telescope needs to be located at a site with low levels of radio frequency interference (RFI). This implies a site that is remote and away from human activity. In bidding to host the SKA, South Africa was required to conduct an RFI survey at its proposed site for a period of 12 months. Apart from this core site, where more than half the SKA dishes may potentially be deployed, the measurement of remote sites in Southern Africa was also required. To conduct measurements at these sites, three mobile measurement systems were designed and built by the South African SKA Project. The design considerations, implementation and RFI measurements recorded during this campaign will be the focus for this dissertation.
Keywords: Radio telescopes; Radio telescopes -- South Africa; Radio astronomy; Radio astronomy -- South Africa; Square Kilometer Array (Spacecraft); Radio -- Interference -- Measurement